Pengaruh Penambahan Serat Pohon Pisang (Musa Paradisiaca) Terhadap Uji Tarik Pada Fiber - Raza Muhamad F; Alvin Vafik Prihatomo; Ryo Kurniawan; Denny Oktavina Radianto (KOLONI, 2023)
Banana trees are included in the Musaceae family, which are herbaceous plants that bear fruit in the tropics. Banana stems are divided into two types, namely true stems and pseudo stems. Most of this banana tree fiber waste is wasted without any initiative from the community to be reprocessed. Natural fiber reinforced composites have the following advantages: light weight, corrosion resistance, water resistance and attractive performance. The aim is to use natural fibers as an alternative material to replace fiber composite materials with banana tree fibers which are more environmentally friendly. Processing of banana tree fiber is washing with water, drying with the help of sunlight for 7 days, and taking fiber manually by cutting it into smaller sizes. Banana trees have a water content composition of 10-15%. Dried banana tree fiber was chemically treated with 10%, 20%, 30% NaOH and ethanol solutions with variations in soaking time of 2, 4, 6 hours, and drying at room temperature. The single fiber test specimen refers to ASTM D 3379 standard. Keywords: Banana tree fiber, composite, fiber tensile strength, specimen